The fantastic in the gabonese short story : Éric Joël Bekale, Jean-Juste Ngomo and Ludovic Obiang - (:unkn) unknown (My University, 2024)
This study aims to explore the fantastic in African literature as a set of events that go beyond understanding. It seeks to show how African authors give resonance to the fantastic as an element of everyday life. This question, combined in the case of contemporary African literary creation of Gabonese short stories (Éric Joël Bekale, Jean-Juste Ngomo, Ludovic Obiang), is relevant because it presents the world of the short story as a universe that reveals that the real and the unreal live together (visible and invisible, day and night, living and dead). Our questioning therefore focuses on the relationship between the fantastic and the real, considering the position of writers in African literature in general, and Gabonese literature in particular. African fantastic literature, unlike Western fantastic literature, reflects current real beliefs in Africa that are presented in the thesis, and the second part focuses on showing how such elements of the real world (rituals, secret societies, water, the temple, iboga, fire, and music) are vectors of cohesion between the ordinary world and the world of spirits. Finally, in the third part, the semiotic and narratological questions specific to the structures of short stories are addressed. The reflection ends with the authors' view of the world, in particular, their critical perspective on the societies in which their characters live.
Keywords: African Research